THE FINTECH BOOK: THE FINANCIAL TECHNOLOGY HANDBOOK FOR INVESTORS, ENTREPRENEURS AND VISIONARIES - Fitri Amalia (Journal of Indonesian Economy and Business (JIEB), 2016)
This book review deals with the fiancial technology area in emerging markets. The followings are the data about the book:Keyword:Publisher:Length:Price:Reading rating:Overall rating:financial technology, emerging marketsJohn Wiley & Sons Ltd, West Sussex, United Kingdom (2016)291 pages$27.16 (paperback)8 (1 = very difficult; 10 = very easy)3 (1 = average; 4 = outstanding)